Analysis Of Differences In Basic Driblling Techniques Undergrade Elementary School Student Basketball - Heri Setiawan; Y Touvan Juni Samodra; Uray Gustian; Rubiyatno; Rahmat Putra Perdana (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2022)
The purpose of this study was to determine the differences in the basic technical abilities of basketball students in grades 1,2,3. The basic technique is the initial ability of the game of basketball where students can learn quickly and understand the game of basketball. The method used is descriptive quantitative analysis method with the type of survey method, this research is carried out by tests and measurements. The research population was students of SDN 10 Anjungan class 1,2,3, which amounted to 117 students, 52 male students, and 65 female students. The technique for taking this sample uses a population sample. The instrument of this research is dribbling zig-gaz. Analysis of the data using SPSS t test was carried out to see if there were differences between classes. The results of this study indicate that the significance value in the lower class is 0.009 <0.05, it can be concluded that in the lower class there is a significant difference in value, it is declared not the same. This study proves that there are significant differences in the basic basketball techniques of the lower class group, such as dribbling.